Antenatal corticosteroids: Sharpening our aim - Vain, Néstor Eduardo (2024)
Since the original study by Liggins and Howie in 1972 that demonstrated that antenatal corticosteroids improved survival in preterm births, obstetricians and neonatologists worldwide progressively adopted this practice.1 This happened much faster in South America, Europe, New Zealand, and Australia than in North America. It took more than 20 years for the American College of Obstetricians and Gynecologists to issue a formal recommendation on their use...